Development of Markov Model for Piping System Reliability Analysis Subjected to Corrosion Under Insulation - Osmira, Nur Husna Anira (IRC, 2016)
A piping system is crucial to any process plant; hence the wall thinning of a piping system in enormously is one of the thread for a processing plant. The efficiency of a plant highly depends on its ability to transport fluid through the pipes to various equipment that function collectively. One of the major contributor to a piping system wall thinning was found to be the effect from the Corrosion Under Insulation (CUI). Piping system that are insulated usually carries hydrocarbon or any hazardous process fluid that requires the system to be in higher temperature from a normal operating temperature. Due to that, CUI is found to be actively deteriorate the system. A continuous deterioration will cause a gradual thinning which leads to leakage and rupture.